From ‘‘crimmigration’’ to ‘‘enemy under-criminalization’’: the Greek case of immigration control - Kourakis, Filippos (The Greek Review of Social Research, 2025)
This essay examines the Greek immigration control system, starting with a brief overview of crimmigration and enemy penology literature. It combines insights from these concepts to introduce the theory of “enemy under-criminalization” which emphasizes the inimical treatment of irregular immigrants without offering them the safeguards of criminal law. The study then identifies key pillars utilized by the Greek state in controlling human mobility at the border. These include immigration detention, pushbacks, and the criminalization of solidarity with immigrants. The essay examines how these mechanisms lack the protections of criminal law, directly treating irregular immigrants as enemies. It concludes by noting the challenges to democracy and the rule of law posed by these practices.